Association of Cognitive Impairment With Anhedonia in Patients With Schizophrenia - Yu, Lingfang; Ni, Hua; Wu, Zenan; Fang, Xinyu; Chen, Yan; Wang, Dandan; Zhang, Chen (Frontiers in Psychiatry, 2021)
Anhedonia is considered as one of the five dimensions of negative symptoms and mainly refers to the reduction of the capacity of feeling pleasure. Increasing evidence suggests that anhedonia in schizophrenia may be partly explained by cognitive impairment. The purpose of this study was to examine anticipatory anhedonia, consummatory anhedonia, and their cognitive associations in schizophrenia. A total number of 100 patients with schizophrenia and 67 healthy volunteers were recruited. The clinical symptoms of schizophrenia were assessed. Anticipatory pleasure, consummatory pleasure, and cognitive functions of each participant were measured. Multiple leaner regression analysis was performed to investigate the influencing factors of anhedonia in schizophrenia. The results showed no significant differences in sex, age, education year, BMI, and marital status between the schizophrenia group and healthy control group (all P > 0.05). Both anticipatory and consummatory pleasure in the schizophrenia group were significantly lower than those in the healthy control group (all P < 0.05). Immediate memory, visual spanning, language, attention, and delayed memory were significantly poorer in the schizophrenia group (all P < 0.001). The results showed that language deficit is an independent risk factor for anticipatory anhedonia (B’ = 0.265, P = 0.008), while delayed memory deficit is an independent risk factor for consummatory anhedonia (B’ = 0.391, P < 0.001). The present study revealed the cognitive associations of anhedonia in schizophrenia. The findings have added new evidence on the influencing factors of anhedonia and provided clues for the associations between clinical manifestations of schizophrenia.